Influx and efflux : writing up with Walt Whitman - Bennett, Jane, 1957- (Duke University Press, 2020)
"In her 2009 book Vibrant Matter, Jane Bennett explored the vital materiality of non-human objects and the deep interrelation of human and non-human forces. Yet she was left with a question: if we recognize human agency as bound up with the agentic forces of the material world, what does that mean for our conception of the self? Bennett's new work, INFLUX AND EFFLUX, draws on the work of Walt Whitman to address this question. Bennett uses Whitman's ideas of composition and decomposition, physical shapes and dispositions, and material and affective influences to posit a processual form of self that can form the basis for a more ecologically oriented and just world. This "democratic personality" is formed through constant influx and efflux (a reference to "Song of Myself") or influence, the way in which the sea, or anything external, comes in, changes things, and leaves again. The first chapter considers Whitman's ideology of "phiz"--A manner or position that affects one's disposition-which for Whitman was linked to the project of egalitarian democracy. Next, Bennett looks at sympathy as a more-than-human atmospheric force-considering the sympathetic currents involved in the transmission of pain, affection, love, and the erotic. Whitman called for his readers to engage in nonchalance and pluralism, instead of applying moral judgement-a stance that Bennett acknowledges might seem to contradict Whitman's ideal of a democratic vista. Yet Whitman assigned his poetry the task of expanding sympathy from the narrow confines of sentiment to a physical force itself. For example, Bennett shows that "I Sing the Body Electric" deliberately evokes a vital flow of sympathy that generates in the reader a sense of the linked value of every body-soul. Rather than directly engaging with the racialized violence of slavery in a way that might make people defensive, Whitman generated a cloud of possibility for abolitionist thought. Bennett concludes by considering Henry David Thoreau's engagements with natural influences-which he calls "the circulation of vitality beyond our bodies"-including sympathizing with trees and exploring psychedelic intoxication. For Bennett, these interactions represent a way of engaging with the more-than-human that recognizes the significant flows of influence that nature has on our lives. Beautifully written and accompanied by Bennett's own drawings and doodles, INFLUX AND EFFLUX will be an important text for scholars in literary theory, political theory, new materialism, philosophy, religion, and critical theory, many of whom would count themselves as Jane Bennett's fans"--